Analisis Faktor Penyebab Perilaku Merokok pada Siswa Remaja Kelas XI di SMP X Surakarta - Desy Rosiana; Dhian Riskiana Putri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to analyze the factors that cause smoking behavior in class XI students at SMP X Surakarta. Smoking behavior among teenagers, especially in school environments, is a significant problem, because it can affect students' physical and mental health. This research uses observation and interview methods with students who are involved in smoking behavior. The results of the research show that the main factors influencing students' smoking behavior are the influence of peers, boredom during class, and the emotional pressure or stress felt by students. Apart from that, family factors also play a role in smoking habits, such as the presence of family members who smoke. Smoking intensity varied between students, with the most frequently chosen smoking areas being hidden areas at school and home. The impacts of this behavior include serious health risks and reduced quality of life. Therefore, this research suggests increasing health education in schools, providing education to parents, strict supervision in the school environment, and providing alternative positive activities for students. It is hoped that this research will provide insight into efforts to prevent smoking among teenagers and create a healthier environment.